Understanding social networking site (SNS) identity from a dual systems perspective: an investigation of the dark side of SNS use. Issue 5 (3rd September 2018) - Polites, Greta L.; Serrano, Christina; Thatcher, Jason Bennett; Matthews, Kevin
Abstract: Using a pathological perspective (e.g., addiction), some research suggests that technology engagement leads to poor self-regulation of behaviours. Rather than pathologise predictors of negative outcomes of IT use, we offer an alternative, identity-based explanation to investigate the role of identity in relation to an individual's perceptions of his/her media use and the potential negative consequences of such use. We build on recent advances in conceptualising IT identity, defined as the extent to which one perceives an IT as central to who he/she is, to explore one's self-identification with social networking sites (SNS) within a broader nomological net of deficient self-regulation, IS habit, use, and normative pressures. Results of a survey of 214 college students indicate that if an individual has strong self-identification with a particular SNS, it will increase perceptions of poor self-control over his/her time. Our study contributes to the literature by highlighting the utility of an identity-based (vs. pathology-based) explanation for such outcomes, which has distinct implications for interventions aimed at improving these outcomes. We suggest future research to advance understanding of IT identity's antecedents and consequences, and discuss practical implications for managing SNS use in workplace and academic settings.